‘The Hungary of the West’ : The Interdependence of the Irish and the Hungarian Constitutional Development during the Last Decades of the Long 19th Century - Szentgáli-Tóth, Boldizsár (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
During the 19th century, several Irish authors looked for those smples from Europe, which might be inwoked during the targeted reconsideration of the Irish-British relationship. The Irish aim was to establish a dualist monarchy with Great Britain, or at least to achieve a broader autonomy within the Empire. For this purpose, Hungary was also often seen as a proper example, how a smaller nation could strenghten its position within a larger country. The Irish constitutional literature, and also the newspapers discussed the compromise between Austria and Hungary in 1867, and called for a similar agreement between Ireland and England to provide broader self-determination for Ireland. The study would outline the main arguments of these contemporary contributions, and would assess, how the real Hungarian development, and a mainly idealized image from Hungary influenced the Irish public discourse during that period. Special highlight would be given to a book published by Arthur Griffith, an important politician of that period, “The Resurrection of Hungary” which provided a detailed narrative from the Hungarian development, and used this sample as an argument in the particular Irish political context. Griffith was also one of the key figures of the negotiations in 1921, which lead finally to the agreement between Ireland and England, therefore, this Hungarian orientation had also clear practical impact. My purpose is to demonstrate this influence on the basis of the original, contemporary Irish sources.